Strategi Pengembangan Desa Wisata Senggigi Dengan Swot Dan Tata Kelola Kolaborasi - Samodra, Vegalyra Novantini; Rosmiati, Rosmiati; Basit, Abdul (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Tourism is a promising sector in the country's foreign exchange earnings, especially with the emergence of tourism villages that are increasingly popular and become a development strategy in many underdeveloped areas. The development of tourism villages through the potential of natural resources, marketing strategies, human resource management, and community participation in all stages of management has the potential to improve the local economy and the standard of living of local communities. In addition, the development of tourism villages can also contribute to environmental conservation and preserve local wisdom. However, to achieve its full potential, it requires infrastructure development, sustainable management of natural resources, effective promotion, development of quality tourism products and services, and involvement and empowerment of local communities. All of these require collaboration from stakeholders to create an independent and sustainable tourism village development strategy. Based on the research method used, namely descriptive qualitative method, this research provides a clear picture of the social situation under study. Primary data were obtained from interviews, field notes, and documentation, while secondary data were obtained from literature studies and documentary data. In addition, semi-structured interview techniques were used to get open opinions and ideas from the informants. This research also uses a descriptive qualitative method. Non-participatory observation techniques to collect data systematically in the form of field notes. In addition, the internal and external factors of the tourism village were analysed using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Then, source triangulation was conducted as one of the methods to check the validity of the data. Then collaboration was carried out using the Collaborative Governance model (TKK) with the Bichler and Lösch model.